Implementation of Reminiscence Therapy for The Elderly at Nursing Home - Witdiawati; Dadang Purnama; Tri Sutrisno (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
As people age, there are several declines in the physiological and psychological functions of the elderly. Where one of them is a decline in cognitive function. Cognitive decline not only affects social life but also the quality of life of the elderly. Reminiscence therapy is one way to help the elderly prevent cognitive decline and dementia. The purpose of this activity is to help the elderly improve their cognitive abilities through activities that can stimulate memory. Method The application of reminiscence therapy with a group approach strategy. The intervention of playing music (singing) and watching movies became the media choices that the team used as reminiscence therapy. The reminiscence therapy activities begin with the identification of the cognitive functions of the elderly participants. The first session of reminiscence therapy is an introduction and singing nostalgic songs. The second session continued with watching movies a Garut historical and historical film of independence. The evaluation session is conducted after each activity session. The results of the activity showed that all the elderly participants were able to recount the historical events depicted in the movies. Reminiscence therapy has proven to be able to evoke the elderly's memories of past events. It is recommended to continue reminiscence therapy activities regularly in a nursing home.